Nilai Religius pada Puisi Sujud Karya K.H. Ahmad Mustofa Bisri - Sari, Siska Amelia; Rafifah, Jihan; Febriana, Vina (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya, 2023)
This study aims to describe the religious value contained in the poem Sujud by K.H. Ahmad Mustofa Bisri through a literary semiotic approach. The method used is a qualitative descriptive method. The source of this research data is an elegy poem by K H. Ahmad Mustofa Bisri entitled